(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
During the experiment, it was found that the morphological, physiological and hematological parameters of the blood of fish kept in bioecological conditions differ depending on the morphophysiological characteristics of the fish organism in the conditions of storage and the hydrochemistry of the water.